Sociological Analysis of the Relationship Between Urban Quality of Life and Social Security and Social Belonging Among Women in the Urban Community of Arak - Bayati, Zahra; Mashhadi, Jila; Yarmohammadtousky, Maryam; Seyyedi, Faranak (Psychology of Woman Journal, 2024)
Objective: The objective of this study was to investigate the relationship between urban quality of life, social security perception, and social belonging among women in the city of Arak. Methods and Materials: A mixed-methods approach was employed, combining quantitative and qualitative data collection and analysis. The study involved a sample of women residing in Arak, with data gathered through structured questionnaires. The analysis was conducted using structural equation modeling (Smart PLS) to examine the relationships between the key variables: urban quality of life, social security perception, and social belonging. Findings: The findings revealed a direct and significant relationship between urban quality of life and social security perception, as well as between urban quality of life and social belonging among women in Arak. The model explained up to 22% of the variance in urban quality of life, with social security perception and social belonging being key predictors. Among the components of these variables, attachment to symbols, norms, values, and economic security were the most influential. Conversely, extreme individualism and public security had the least impact on the model. Conclusion: The study concludes that urban quality of life for women in Arak is significantly influenced by their perception of social security and their sense of social belonging. These factors are interdependent and contribute to the broader social cohesion and well-being within the community. Enhancing these elements could lead to improved urban quality of life, particularly by fostering social connections and ensuring a secure and supportive environment for women. The findings underscore the importance of addressing these variables in urban planning and policy-making to promote sustainable and inclusive development.